BLOOD AND SEMINAL PLASMA MINERAL PROFILE OF BUFFALO BULLS IN RELATION TO FERTILITY - MAVI, P S; SIDHU, S S; BAHGA, C S; KUMAR, RAVI; SINGH, NARINDER; SINGH, PRAHLAD (The Indian Journal of Animal Reproduction, 2010)
Eleven healthy Murrah buffalo bulls were divided into two groups on the basis of their fertility i.e. low fertile and high fertile (conception rate< 30% and >30%). The average conception rate In low and high fertile groups was 24.1 and 34.02, respectively. Blood serum and seminal plasma were analyzed for various micro elements. Blood serum zinc, manganese and iron were higher by 5.63, 10.17 and 14.11 percent in high fertile than low fertile group. Similarly seminal plasma zinc, manganese and iron were higher by 10.31, 2.71 and 10.47 percentin high fertile compared to low fertile group. Blood serum and seminal copper was lower by 8.99 and 7 .14 per cent in high fertile from low fertile group respectively. Concentration of copper and manganese In blood serum and seminal plasma showed significant differences (P<0.05), where as zinc and iron did not differ significantly. Seminal plasma zinc, copper and serum zinc were positively correlated (P<0.05) with conception rate (r =0.605, 0.672 and 0.708) respectively. Blood serum zinc was positively correlated (r = 0.887) with seminal plasma zinc. Seminal characteristics did not differ significantly in the two groups. It can be concluded that physical characteristics of semen cannot be taken as index and more emphasis should be laid on conception rate. Blood and seminal plasma zinc, manganese and iron levels could be taken as indices offertility in buffalo bulls.